(untitled) (Academic Journal of Internal Affairs, 2020)
The paper reports about an empirical research in 2018. The aim of the investigation was to get a picture about characteristic reasons and cases for refusal of report and for termination of investigation. According to official statistical data was the number of cases increased when infancy or insanity inhibited opening of a criminal process. This is clear to see in the research, too.